Electroacupuncture Improves Choroidal Blood Flow to Inhibit the Development of Lens-Induced Myopia in Guinea Pigs. (24th June 2022) - Yu, Ting; Xie, Xiaofeng; Wei, Huixia; Wu, Qiuxin; Zhang, Xiuyan; Tian, Qingmei; Song, Jike; Bi, Hongsheng
Abstract : Introduction . The purpose of this paper was to study the effect of electroacupuncture (EA) on choroidal blood flow (ChBF) in a guinea pig model of lens-induced myopia (LIM). Methods . Guinea pigs were randomly divided into 4 groups: normal control (NC) group, LIM group, LIM + electroacupuncture (LIM + EA) group, and LIM + sham acupoint (LIM + sham) group. Right eyes were covered with a −6D lens to induce myopia. Meanwhile, LIM + EA group and LIM + sham group were treated with EA at acupoints Hegu (LI4) and Taiyang (EX-HN5) and sham points. Refraction, axial length (AL), choroidal thickness (ChT), vessel density of choriocapillaris (CC) and choroidal layer, and scleral collagen fiber were measured. Besides, hypoxia-inducible factor-1 α (HIF-1 α ), matrix metalloprotein-2 (MMP-2), and tissue inhibitor metalloprotease-2 (TIMP-2) expression in sclera were detected. Results . Refraction and AL were significantly decreased and ChT and vessel density of CC were significantly increased in LIM + EA group at 2 weeks and 4 weeks (all P < 0.05 ) compared with LIM group. However, no significant difference of vessel density of choroidal layer was observed between LIM and LIM + EA group at 2 weeks and 4 weeks. Scleral collagen fibrils diameters were significantly increased in LIM + EA group at 4 weeks (P < 0.001 ) compared with LIM group. At the end of experiment, the mRNA and protein expression of HIF-1 α and MMP-2 were significantly decreased (all P < 0.05 ) and those of TIMP-2 were increased in LIM + EA, compared with LIM. However, there were no significant differences between LIM and LIM + sham group. Conclusions . EA can improve the vessel density of choroid and then possibly improve scleral hypoxia, which may inhibit the growth of the AL in myopia guinea pig.